Lectotypifications and taxonomic changes in Brazilian Crotalaria L. (Leguminosae) - Flores, Andréia Silva; Rockinger, Alexander; Rodrigues, Rodrigo Schütz; Tozzi, Ana Maria Goulart De Azevedo (Phytotaxa, 2016)
As part of a revision of the species of Crotalaria L. (Papilionoideae, Crotalarieae) occurring in Brazil, eleven lectotypifications are proposed for: Crotalaria acutiflora Benth., Crotalaria depauperata Mart. ex Benth., Crotalaria holosericea Nees & Mart., Crotalaria holosericea var. grisea Benth., Crotalaria laeta Mart. ex Benth., Crotalaria leptophylla Benth., Crotalaria rufipila Benth., Crotalaria unifoliolata Benth., Crotalaria vitellina Ker-Gawl., Crotalaria vitellina var. glabrata Benth., and Crotalaria vitellina var. minor Benth. Four new synonyms are also proposed.